The Scope of the Pauline Action - Nicolae, Fala (Journal of Danubian Studies and Research, 2022)
The modernization of the Civil Code of the Republic of Moldova has brought with it several legislative innovations, among which is the Pauline action (revocation). The scope of Pauline’s action covers, in principle, all civil legal acts, regardless of the category to which they belong. From a practical point of view, the determination of the Pauline action’s application scope relies in the identification of exceptions to the general rule. The revocation action’s application scope has limitations resulting from the methods and forms of defense of subjective civil rights and the competition between these methods. The object of the Pauline action can be only a valid and efficient legal act, which means that if there are grounds for nullity or inefficiency, applicable will be the methods of finding or declaring nullity, finding inefficiency, finding simulation. From the perspective of determining the Pauline action’s application scope, it is relevant to address certain legal acts or facts that provoke doctrinal controversy - declaring the unenforceability of a payment made in the benefit of the creditor by the debtor; the possibility of challenging the court decision by prejudiced creditors through a Pauline action as a result of the debtor’s fraudulent procedural behavior. The institution of Pauline action holds sufficient „elasticity” to ensure a veritable protection against various fraudulent legal acts to which the debtor may resort to.